The Polish-German Border in the Light of the 2+4 Treaty and the Polish-German Treaty on the Confirmation of the Border between Them (Polish Yearbook of International Law, 2023)
The essence of the “border problem” between Poland and the FRG reaches back to the provisions of the Potsdam Agreement of 1945. The Polish position as unambiguous from the beginning: the border on the Odra and Nysa Łużycka rivers was established under international law in the Potsdam Agreement, hile the subsequent actions undertaken within the framework of the “peace settlement” could only have complementary, declaratory signifcance. On the other hand, in the FRG an ofcial legal position was developed according to which the former eastern German territories were only given to Poland (and the USSR) “under their administration”, and the fnal decision on the border was left to be taken by the future unifed Germany in a “peace treaty” or a “peace settlement”. This position was not changed by the Normalization Treaty between Poland and the FRG of 1970, because it was interpreted in the FRG as only a “treaty about the renunciation of force”, an element of a modus vivendi which was to last until the unifcation of Germany. On the other hand, the gorzelec Treaty of 1950 between Poland and the GDR was interpreted as not binding for the future unifed Germany. Such a position deeply destabilized political relations between the FRG and Poland in the post-war period and had a conﬂict-generating signifcance in a number of areas. At the beginning of 1990 the political changes in Poland coincided with the process of German unifcation. The democratic opposition in Poland, and thereafter the government of Tadeusz Mazowiecki, unequivocally supported the right of the German people to self-determination, at the same time expecting an unequivocal position on the Polish-German border. This fundamental problem was closed in 1990 under two international agreements: the Treaty on the Final Settlement with Respect to Germany (2+4 Treaty) and the Treaty between the Federal Republic of Germany (united Germany) and the Republic of Poland on the confrmation of the border between them. Thus for thirty-plus years now the “border problem” has been removed from the agenda of political discussions in Polish-German relations, which proves the eﬀectiveness and durability of the agreement reached, which was reﬂected in both treaties.